INFLUENCE OF ADDING DIFFERENT PARTICLES FILLERS ON ELECTRICAL CONDUCTIVITY AND MECHANICAL PROPERTIES OF HIGH DENSITY POLYETHYLENE (HDPE) MATRIX COMPOSITES - SADAN, MAHDI KHIDER (Journal of Duhok University, 2023)
Mechanical and electrical conductivity properties of high density polyethylene (HDPE) with three different parctical fillers [aluminum oxide (Al2O3), met coke ash (MCA), Nano fibrillated composite (NFC)] composites were evaluated with relation to the influence of the reinforcement materials content. The reinforcement (10% wt.) in the matrix. Forming the sample groups P1, P2, P3, P4, P5, and P6. After processing, the composites were evaluated by Shore D hardness, electrical conductivity, and charpy impact. Clear effect in the mechanical and electrical conductivity test factors was recorded depending on the particles reinforcement type and its percentage added to the Polymer. No experimental difficulties were demonstrated in any composite, and these difficulties are attributed to the phase separation that makes area possible to treat in it was found that an extruder of normal. Results showed that the best improvement in hardness occurs at (80% HDPE+10 % Al2O3, 10% met coke ash). The highest conductivity occurs also at (80% HDPE+10 % Al2O3, 10% met coke ash). The highest impact test occurs at (100% HDPE); this means that the reinforcement did not improve the impact properties.